Assessment of Riverbank Erosion and Accretion and its Impact on the People of Chairman Ghat, Noakhali, Bangladesh - Mou, Momotaj Ara; Tusar, Md. Kamruzzaman; Haque, Md. Riyadul; Chakraborty, Shemoul; Ahmed, Sajib (Journal of Sustainability and Environmental Management, 2023)
Nestled within the vastness of the Meghna deltaic plain, Noakhali, and in particular, Chairman Ghat, stand as poignant examples of Bangladesh’s intricate relationship with environmental challenges. The significance of the Meghna deltaic plain cannot be overstated, as it shapes the very fabric of the nation’s landscape. However, this geographic richness comes hand-in-hand with vulnerability, and nowhere is this more apparent than in the relentless grip of riverbank erosion. Chairman Ghat, in Noakhali, epitomizes the struggle against this natural force, making it a focal point for understanding and addressing the profound impact of riverbank erosion in the region. The primary objective of this research work is to assessing river bank erosion & accretion and examine its the potential impact in the chairman Ghat area. In order to achieve this goal, this study employs remote sensing and GIS techniques to assess the erosion and accretion rates of Chairman Ghat on the Noakhali coast from 2000 to 2022 and conduct household survey to examine the socioeconomic impacts of river erosion on the local population. The findings revealed that Over the past 22 years, the Meghna estuary experienced a total of 667.0 km2 of erosion and 689.1 km2 of accretion. Chairman Ghat area alone witnessed a net erosion rate of 4.2 km2 per year during the specified period, resulting in a loss of 117.7 km2 of land, while only 25.3 km2 of new land was added. From household survey it is found that the adverse effects of riverbank erosion on the local community are evident, leading to the loss of vital agricultural lands, homesteads, and property damage that cannot be easily recovered. Consequently, a significant portion of the affected population is compelled to migrate, thereby exacerbating their socio-economic plight as they are forced to change professions. This research sheds light on the extent of riverbank erosion in Chairman Ghat, Noakhali, and elucidates its profound socioeconomic implications on the lives of the local inhabitants. The findings of the study will help to enhance our understanding of the specific impact of river erosion enabling the development of targeted strategies to protect vulnerable communities’ lives, livelihoods, and environments. It will also promote cohesive coastal zone management, implementing robust measures that counteract the destructive consequences of riverbank erosion, thereby ensuring the sustainable development and resilience of these crucial ecosystems.